1991
DOI: 10.1073/pnas.88.13.5749
|View full text |Cite
|
Sign up to set email alerts
|

DNA strand-specific mutations induced by (+/-)-3 alpha,4 beta-dihydroxy- 1 alpha,2 alpha-epoxy-1,2,3,4-tetrahydrobenzo[c]phenanthrene in the dihydrofolate reductase gene.

Abstract: DNA strand-specific mutations induced by (+)-3a,4.6-dihydroxy1a,2a-epoxy-1,2,3,4-tetrahydrobenzo[c] ABSTRACT We previously showed that the preferred mutation induced by (±)-3a,4.8-dihydroxy-la,2a-epoxy-1,2,3,4-tetrahydrobenzo[cJphenanthrene (BcPHDE) in the dihydrofolate reductase gene in Chinese hamster ovary cells was a purine to thymine transversion on the nontranscribed strand at the sequence 5'-RRR-3' (R is a purine and the mutated base is underlined). To determine whether the observed mutational stran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
1
11
1
Order By: Relevance
“…In several studies of mutation in cultured mammalian cells, it has been observed that the nontranscribed strand is much more prone to mutation by agents that produce bulky adducts or pyrimidine dimers (8,16,77,81). Our data are also consistent with this finding.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…In several studies of mutation in cultured mammalian cells, it has been observed that the nontranscribed strand is much more prone to mutation by agents that produce bulky adducts or pyrimidine dimers (8,16,77,81). Our data are also consistent with this finding.…”
Section: Resultssupporting
confidence: 82%
“…Mutations at 5 of the 7 less-well-conserved positions were found; more often than not, the phenotype was severe, with little or no correctly spliced transcripts detected (NS79, 42,8,91, and 90 at -3, -2, -1, +3, and +4, respectively). No mutants were isolated that affected positions +5 or +6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whatever the origin of this unexpected bias, it could explain why the lack of CPD repair in the nontranscribed strand in XP129 cells does not greatly increase the frequency of 6-thioguanine resistance. In contrast to the results for repair-deficient mutants, strand-specific mutational analysis in repair-proficient hamster and human cells reveals a strong bias for mutations resulting from lesions in the nontranscribed strand (4,15,18,32). These results suggest that preferential repair of the transcribed strand exerts a substantial influence on UV-induced mutagenesis.…”
Section: Discussioncontrasting
confidence: 48%
“…This mutational preference re¯ects the propensity of BPhDE to react primarily with G and A in DNA, as well as the tendency of these adducts to mispair with adenine during replication (14). A strand bias in mutations was also observed for racemic anti-BPhDE, with the non-transcribed strand giving rise to most of the mutations (15).…”
Section: Introductionmentioning
confidence: 89%